BIOETIK PEMANFAATAN SUMBERDAYA GENETIK MIKROBA - Sutanto, Agus (Bioedukasi Jurnal Pendidikan Biologi, 2010)
Human civilization will contruct interaction between human and their god, their fellow, and their environment. In traditional grow local wisdom which contain bioethic that universal and that contain negative in use and manage resource around them, traditional bioethic inclined ignored and undergo erosion. In growth of IPTEK (Science and Technology) and using biotechnology that being acceleration of changing of social-economy living that dynamic and complex in transaction form, or service at living things or they parts, were need antisipation for value order or bioethic that satisfaction.Kata kunci: bioetik, tata nilai